A Case Study on Ayurvedic Management in PCOS - Shahina Mole.S; Ammu.K.Sasi (International Journal of Ayurveda and Pharma Research, 2021)
Female reproductive system consists of hypothalamo-pituitary-ovarian axis and intact uterine-adnexa which maintains a complex mechanism. In human body all the systems are interrelated to function properly; any imbalance in one system may cause multisystem pathogenesis. Polycystic ovarian syndrome (PCOS) is a common endocrinopathy, which is multifactorial and polygenic condition, manifested as oligoovulation or anovulation, signs of hyperandrogenism and multiple small ovarian cysts. Signs and symptoms vary within individual’s overtime. This adversely affect the reproductive system by menstrual disorders, infertility, obesity, depression, sleep apnea, insulin resistance and in due course may result in diabetes mellitus, endometrial cancer, cardiovascular disease etc. According to Ayurveda PCOS is a disorder which involves the three Doshas, Dhathus like Rasa, Raktha and Medas. The Srothas involved in this condition are Rasa, Rakta and Arthava vaha which eventually manifests features such as Anarthava (amenorrhea), Vandhyathwa, Pushpagni, Abeeja rtuchakra (anovular bleeding). Here is a case report of 19 year old girl who presented with irregular menstruation, rapid weight gain and hair loss. On USG she was detected to have bilateral PCO pattern. Based on the clinical features, treatment principles adopted were Aamapachana, Vata anulomana, Kaphapittahara and Arthava janana. After 2 months of internal medications, symptoms reduced markedly and menstruation was normal. Adherence to Ayurvedic principles is found to be helpful in PCOS for a healthy and fruitful life.